Poly(ester amide)-based hybrid hydrogels for efficient transdermal insulin delivery. Issue 42 (5th October 2018) - Zhang, Shaohan; Xin, Peikun; Ou, Qianmin; Hollett, Geoffrey; Gu, Zhipeng; Wu, Jun
Abstract : Transdermal drug delivery is an attractive, non-invasive treatment. Abstract : Transdermal drug delivery is an attractive, non-invasive treatment. It can avoid first-pass hepatic metabolism and provides the possibility of self-administration. Hydrogels are promising biomaterials due to their important qualities such as biocompatibility and biodegradability. Recently, there has been tremendous growth in the area of hydrogels for transdermal drug delivery. In this work, a new kind of arginine-based poly(ester amide) (Arg-PEA) and polyethylene glycol diacrylamide (PEG-DA) hybrid hydrogel was developed for transdermal drug delivery. The hydrogels not only possess excellent swelling capacity, but also have good mechanical properties, which were then evaluated as drug delivery agents using insulin as a model system. Cytotoxicity testing and in vivo skin irritation tests demonstrated that the hydrogels were biocompatible. Finally, the results indicated that the prepared hydrogels could not only perform transdermal drug delivery, but also might regulate blood glucose levels in a mouse model with streptozotocin-induced diabetes.